Mentors for beginning teachers as middle leaders: the messy work of recontextualising. (8th August 2019) - Willis, Jill; Churchward, Peter; Beutel, Denise; Spooner-Lane, Rebecca; Crosswell, Leanne; Curtis, Elizabeth
ABSTRACT: Mentors for beginning teachers in schools are often unacknowledged middle leaders in their schools. Through their work with beginning teachers, they not only provide local leadership in their contexts, they influence and shape the work of the next generation of teachers. Government-funded mentor training for the purpose of supporting beginning teachers in Education Queensland schools commenced in 2014 (Queensland Government. [2017]. Mentoring Beginning Teachers . http://education.qld.gov.au/staff/development/employee/teachers/mentoring.html ). In Queensland, Australia, over 3000 experienced teachers have completed a two-day professional learning Mentoring Beginning Teacher (MBT) programme. Upon completion, mentors were expected to design and enact a mentoring programme that met the beginning teachers' needs in their context, using the dialogic mentoring principles they had learned to fulfil the policy goals of increasing the number of beginning teachers transitioning to full registration. This article draws on Bernstein's ([2000]. Pedagogy, Symbolic Control, and Identity: Theory, Research, Critique . Revised ed. Rowman & Littlefield) concepts of recontextualisation, and horizontal and vertical discourses of knowledge to understand how mentor teachers negotiated and enacted their roles as middle leaders in schools in diverse schooling contexts.